A Canadian Physician Survey of Dyspepsia Management. (1st February 1998) - Chiba, Naoki; Bernard, Lisa; O'Brien, Bernie J; Goeree, Ron; Hunt, Richard H
Abstract : OBJECTIVE: To determine the management of patients with new onset dyspepsia by Canadian family physicians. METHODS: A survey was mailed to 195 family physicians in August 1995 to identify how they manage dyspepsia in patients according to four scenarios: based on presenting symptoms alone; assuming Helicobacter pylori -positive; known to be H pylori -negative; and endoscopically confirmed nonulcer dyspepsia. RESULTS: A total of 170 of 195 physicians (87.2%) completed the survey. Physicians reported that 7.3% of their practice is devoted to dyspepsia and 23% of these dyspeptic patients present for the first time. Ninety-three per cent of family physicians find a symptom classification of ulcer-, reflux- and dysmotility-like dyspepsia helpful. The majority of patients are advised to make lifestyle changes and are treated with antacids or empiric drug therapy. A H2 receptor antagonist was the drug of choice for ulcer and reflux-like dyspepsia, while prokinetics were often used for reflux and dysmotility-like dyspepsia. After failure of initial treatment, patients were given another course of empiric treatment, commonly with cisapride or omeprazole. Family physicians estimated that the mean time to obtain a gastrointestinal consult was five weeks, and 70% indicated that this time to consult adversely influenced their decision to refer. If this time was reduced to less than two weeks, responding physicians would consider referring all eligible patients. On average, two to 2.5 courses of empiric therapy were given before referral. If H pylori status was known, fewer empiric treatments (mean 1.8) were given before gastroenterological referral compared with the other scenarios. If the patient had nonulcer dyspepsia, 30% of family physicians provided reassurance only and did not prescribe empiric drug treatment. CONCLUSIONS: Most newly dyspeptic patients in Canada are treated with empiric therapy according to symptom classification and referred for endoscopy after an average two to 2.5 treatment courses.